-4(-4-6x)=88

Simple and best practice solution for -4(-4-6x)=88 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-4-6x)=88 equation:


Simplifying
-4(-4 + -6x) = 88
(-4 * -4 + -6x * -4) = 88
(16 + 24x) = 88

Solving
16 + 24x = 88

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 24x = 88 + -16

Combine like terms: 16 + -16 = 0
0 + 24x = 88 + -16
24x = 88 + -16

Combine like terms: 88 + -16 = 72
24x = 72

Divide each side by '24'.
x = 3

Simplifying
x = 3

See similar equations:

| 3x-8=58-2x | | 3(4x-1)-7x=16 | | 5x+26+14x=82 | | 2x^2+8=32 | | 3^(-4)/3 | | 32-3x=6x+21 | | x/7 | | 5x-8=2x+29 | | 3+5x+5x=83 | | 7x+2=4-(4x-7) | | 222-4x=179-44x | | 4x+7=x-5 | | -39-6x=-8x+11 | | 10/21=2a/a+b | | 10x-114=5x-14 | | 3x+7=-48-8x | | 160-4x=6x+10 | | 1ox-114=5x-14 | | 18p+33= | | 3x-9+7x=101 | | 3a+2a=9 | | 2x-1=10x-50 | | 1=2r+9 | | -69=-3x-4(3x-3) | | 3(5x+2)=24 | | 11/3=v/8 | | 90-2x=25+18 | | 5x+8=-78-9x | | -6x+3(x+3)=36 | | 5x+27=4x-72 | | 6(3x-7)-3=6(x-3)+45 | | 69=-4x-5x+6 |

Equations solver categories